Consumer Preferences for Eating Quality of USDA Prime Beef Differentiated into Tiers - Chesney A. Effling (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to evaluate consumer palatability preferences in strip loin steaks of upper 2/3 Prime when compared to Low Prime, upper 2/3 Choice, and Low Choice cooked to three degrees of doneness (DOD). Study Description: Beef strip loin steaks from four marbling categories (upper 2/3 Prime [Super Prime], Low Prime, Top Choice, and Low Choice) were cooked to one of three DOD (Rare = 140°F, Medium = 160°F, and Well-done = 170°F) on an electric flat top grill. Flip and pull temperatures for the steaks were specific to each DOD. Consumers evaluated samples for juiciness, tenderness, flavor, and overall liking using a 100-point line scale and indicated acceptability for each trait. Responses were recorded using a digital survey on an electronic tablet. The Bottom Line: These results indicate consumers prefer the eating quality of Super Prime steaks and support the need for a premium program within the Prime grade, offering the beef industry an opportunity to capture added value from this highest-grade within beef.
Keywords: beef; consumer; USDA Prime